Tabletop RPG Design in Theory and Practice at the Forge, 2001–2012 - White, William J. author. aut Link
XXI, 268 p. 9 illus., 2 illus. in color.
Keywords: This book provides an introduction to the Forge, an online discussion site for tabletop role-playing game (TRPG) design, play, and publication that was active during the first years of the twenty-first century and which served as an important locus for experimentation in game design and production during that time. Aimed at game studies scholars, for whom the ideas formulated at or popularized by the Forge are of key interest, the book also attempts to provide an accessible account of the growth and development of the Forge as a site of participatory culture. It situates the Forge within the broader context of TRPG discourse, and connects “Forge theory” to the academic investigation of role-playing. William J. White (Ph.D., Rutgers, the State University of New Jersey) is Associate Professor of Communication Arts & Sciences at Penn State Altoona, USA. He is a contributor to Role-Playing Game Studies: Transmedia Foundations (2018) as well as Analog Game Studies, and an editor of the International Journal of Role-Playing.